Principi elementari di reologia dei polimeri: Parte I: fluidi non-Newtoniani - Villani, Vincenzo (Chimica nella Scuola, 2023)
In Elementary Principles of Polymer Rheology, found in the Keywords section of this issue, the fundamentals of viscosity of polymer materials have been introduced and pseudoplastic, dilatant, thixotropic, rheopectic, and plastic non-Newtonian behaviors have been discussed. In this contribution some significant cases of non-Newtonian behavior of common polymers will deal with. It is a very vast subject which often, due to its complexity, is not explored in school programs, but whose knowledge is increasingly required in current technological applications.